Membrane compaction in forward osmosis process - Ng, Daniel Yee Fan (2021)
Membrane compaction is commonly observed in polymeric membranes when subjected to elevated hydraulic pressure, but was rarely discussed in forward osmosis (FO) processes, since there was usually little hydraulic pressure difference across the membrane. In the current study, three TFC membranes were fabricated using hollow fiber substrates with varied water permeability to study the effect of the osmotic pressure on the TFC membranes. The TFC membranes were continuously tested in FO experiments for 24 h by using DI water as feed and NaCl solutions of different concentrations as draw solution, and their performances were checked again using fresh feed solutions. At the end of FO experiments, all TFC membranes experienced water flux and salt flux decline to different extents. The TFC membranes were characterized using SEM, TEM and AFM. Visible changes in the cross-section morphology and surface topography of the TFC membranes were observed after FO experiments. The observation suggested that the occurrence of membrane compaction could be associated with “negative pressure” build-up within the support layer of the TFC membranes. The current study could shed light on the important factors that should be considered during membrane fabrication and when establishing the testing protocols for the characterization of FO membrane.